2008
DOI: 10.1002/dvg.20362
|View full text |Cite
|
Sign up to set email alerts
|

Development of a pituitary‐specific cre line targeted to the Pit‐1 lineage

Abstract: Tissue-specific expression of the Cre recombinase is a well-established genetic tool to analyze gene function in specific tissues and cell types. In this report, we describe the generation of a new transgenic line that expresses Cre under the control of the rat growth hormone releasing hormone receptor (rGhrhr) promoter. This promoter, chosen to target the anterior pituitary, drives cre-mediated recombination in cells of the Pit1 lineage, including somatotrophs, lactotrophs, and thyrotrophs. Cre activity is fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
(34 reference statements)
0
17
0
Order By: Relevance
“…In line with these data, TEC3KO tumors revealed heavy staining for this marker by immunohistochemistry, even in areas where cell proliferation was not obvious ( Figure W3C ). The heterogeneity of these tumors was further observed by LacZ staining of frozen tissue sections taken from TEC3KO animals carrying the Rosa26 lacZ allele [22]. Analysis of this staining revealed that both cre-positive and cre-negative cells were present in the tumors, further confirming their heterogeneity ( Figure W3D).…”
Section: Histopathology Of Tec3ko Tumorsmentioning
confidence: 58%
See 2 more Smart Citations
“…In line with these data, TEC3KO tumors revealed heavy staining for this marker by immunohistochemistry, even in areas where cell proliferation was not obvious ( Figure W3C ). The heterogeneity of these tumors was further observed by LacZ staining of frozen tissue sections taken from TEC3KO animals carrying the Rosa26 lacZ allele [22]. Analysis of this staining revealed that both cre-positive and cre-negative cells were present in the tumors, further confirming their heterogeneity ( Figure W3D).…”
Section: Histopathology Of Tec3ko Tumorsmentioning
confidence: 58%
“…LacZ staining of frozen tissues was performed as described (Yin et al, 2008). Images were visualized on an Olympus BX50 microscope and captured using Spot Basic v4.1 software.…”
Section: Supplemental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These mice carried the ROSA26 lacZ reporter allele in order to confirm cre expression by LacZ staining (18) (Supplemental Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we produced a mouse line which used the rat GHRH receptor promoter to drive cre expression. This promoter, which is normally specific for the GH-producing pituitary cells [31], enabled expression of cre in cells of the Pit1 lineage, including somatotrophs, lactotrophs, and thyrotrophs [32]. These mice were then crossed with Prkar1a conditional null animals [26] to produce mice with a pituitary-specific knockout of Prkar1a (Prkar1a-pitKO) [33].…”
Section: Mouse Models Of Prkar1a Inactivationmentioning
confidence: 99%